2020
DOI: 10.1200/jco.2020.38.15_suppl.4100
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of VOLTAGE-A: Nivolumab monotherapy and subsequent radical surgery following preoperative chemoradiotherapy in patients with microsatellite stable and microsatellite instability-high locally advanced rectal cancer.

Abstract: 4100 Background: Chemoradiotherapy (CRT) followed by radical surgery (S) is standard therapy for patients (pts) with locally advanced rectal cancer (LARC). Sequential use of an anti-PD-1 antibody after radiation demonstrates synergistic effects in in vivo models, and an anti-PD-1 antibody is effective in pts with microsatellite instability-high (MSI-H) metastatic colorectal cancer (mCRC). We studied nivolumab (nivo) and radical S following CRT (50.4 Gy with capecitabine 1,650 mg/m2) in T3–4 NanyM0 LARC. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 0 publications
2
60
0
Order By: Relevance
“…To note, similar histological results have been reported for patients with the resection of residual lesions after ICI treatment for metastatic MSI/dMMR CRC [67,68]. In the phase II VOLTAGE-A study evaluating nivolumab followed by radical surgery after chemoradiotherapy for patients with rectal cancer, 60% of complete pathological responses were observed among MSI/dMMR cases (three out of five) [69].…”
Section: Moving Forward With the Niche Studysupporting
confidence: 71%
“…To note, similar histological results have been reported for patients with the resection of residual lesions after ICI treatment for metastatic MSI/dMMR CRC [67,68]. In the phase II VOLTAGE-A study evaluating nivolumab followed by radical surgery after chemoradiotherapy for patients with rectal cancer, 60% of complete pathological responses were observed among MSI/dMMR cases (three out of five) [69].…”
Section: Moving Forward With the Niche Studysupporting
confidence: 71%
“…In addition, immune checkpoint inhibitors such as durvalumab, avelumab, and nivolumab and other novel agents such as peposertib, a DNA protein kinase inhibitor, and aflibercept, an angiogenesis inhibitor, are being investigated in a TNT setting. 32 , 33 , 34 , 35 , 36 A list of recent and ongoing TNT trials that are yet to be published is included in eTable 2 in the Supplement . 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…For example, clinical trial evidence from lung cancer has shown that survival is increased when immune checkpoint inhibition is delivered after radiation in the stage III setting. [110] Preliminary findings from the VOLTAGE-A trial in LARC [115] also showed encouraging results with sequential treatment. In contrast, preclinical evidence from Dovedi et al [101] implies that earlier use of immunotherapy and specifically its combination with radiation may lead to improved responses.…”
Section: Local Effectsmentioning
confidence: 96%
“…Given the potential overlapping adverse reactions with combination treatment, the safety data from these trials are eagerly awaited. To date, there have been encouraging results from the VOLTAGE trial (NCT02948348; see Table 2) [115] in which of 39 patients, no grade 4 nivolumab-related adverse events were recorded and all severe immune-related adverse events had fully resolved before surgery. Accounting for the one patient who refused surgical resection following a complete clinical response to treatment, 38 (97%) of 39 patients proceeded to radical surgery.…”
Section: Current Evidence and Ongoing Trials Investigating Checkpointmentioning
confidence: 99%